Pengaruh Brand Image dan Harga terhadap Loyalitas Penggunaan Paket Data Internet Telkomsel pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Sumatera Utara - Pramulia, Anggi; Helmi, Tengku Ahmad; Julkarnain, Julkarnain (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This study aims to determine the effect of brand image and price on loyalty of Telkomsel Internet Data Package users in students of the Faculty of Economics and Business UISU Medan. The population of this study were 160 students of the Faculty of Economics and Business UISU Management. Study Program, sampling using the Slovin formula obtained a sample size of 62 samples and allocated to each stratum using the proportional random sampling formula, the data was analyzed using the SPSS 20 program. Based on the research results, it can be concluded that the brand image variable has a significant effect on user loyalty while the price variable has no significant effect on user loyalty, brand image and price have a significant effect on user loyaltys performance